First detection of VEB-1 extended-spectrum β-lactamase-producing Escherichia coli clinical isolate in Japan - Junko Shindou; Wataru Hayashi; Shizuo Kayama; Liansheng Yu; Hui Zuo; Yo Sugawara; Motoyuki Sugai (Microbiology Spectrum)
ABSTRACT The extended-spectrum β-lactamase (ESBL) gene, blaVEB-1, was identified for the first time in an Escherichia coli clinical isolate, JARB-RN-0061, from blood cultures in a Japanese general hospital in 2021. The isolate exhibited high resistance to broad-spectrum cephalosporins, including ceftazidime (MIC >128 mg/L) and cefepime (MIC = 16 mg/L). blaVEB-1 was identified during whole-genome sequencing and characterization of the isolate. JARB-RN-0061 belonged to the B2-O2:K1:H7-ST95-fimH41 lineage and was classified as presumptive extraintestinal pathogenic E. coli (ExPEC) and uropathogenic E. coli (UPEC). Moreover, the strain harbored multiple virulence genes on the chromosome. The Col156/IncFIB(AP001918)/IncFII(29)-type plasmid (114,216 bp), with clbB and tcpC genes involved in bacteremia, was unique to the fimH41 subclone. The blaVEB-1 gene was located on a non-typeable and non-conjugative plasmid, pJARB-RN-0061_VEB-1 (17,093 bp). It was embedded in the class 1 integron In1883-like, with multidrug resistance gene cassettes for aacA4, aadB, cmlA5, qnrVC4, and dfrA14. Notably, comparative analysis of the complete sequence of plasmid pJARB-RN-0061_VEB-1 revealed that it was highly homologous to the blaVEB-1-harboring plasmid, pMS2H7VEB-1 (100% coverage and 99.99% identity), except for the Tn3 family transposon (4,931 bp) and the plasmid pRHBSTW-00138_5 (97% coverage and 100% identity) harbored by Klebsiella quasipneumoniae subsp. similipneumoniae strains from hospital sewage in Japan and wastewater influent in the United Kingdom, respectively. The emergence of a human pathogenic E. coli clinical isolate with the blaVEB-1-carrying plasmid in the B2-ST95 worldwide pandemic lineage, characterized by the virulence potential of ExPEC or UPEC but a low prevalence of antimicrobial resistance, would raise public health concerns.IMPORTANCEESBLs are plasmid-mediated enzymes that confer resistance to clinically significant antimicrobial agents, such as broad-spectrum cephalosporins. Recently, the rapid spread of CTX-M-type ESBL-producing E. coli has become a global issue, including in Japan, where ESBL production in human pathogenic E. coli, such as the ExPEC and UPEC lineages, which typically harbor several virulence genes, is a severe public health concern. To date, VEB (Vietnamese extended-spectrum β-lactamase) producers have been found only in hospital wastewater and rivers in Japan. Thus, we describe the first detection of a very rare human-derived blaVEB-1 gene in the E. coli B2-ST95 pandemic clonal lineage that is highly associated with ExPEC and UPEC in a Japanese clinical setting. Furthermore, we characterized the genomic features of plasmids harboring the class 1 integron-borne blaVEB-1. Our findings highlight the significance of closely monitoring ESBL-producing E. coli isolates to prevent the potential dissemination of this resistance determinant in Japan.